Dark city [videorecording (DVD)] - Proyas, Alex, 1963-; Dobbs, Lem; Goyer, David S.; Sewell, Rufus, 1967-; Sutherland, Kiefer, 1966-; Connelly, Jennifer; O'Brien, Richard, 1942-; Richardson, Ian, 1934-2007; Hurt, William; Friels, Colin, 1952-; Butel, Mitchell; Gallacher, Frank, 1943-2009; et al. (New Line Home Entertainment, 2008)
When John Murdoch wakes with no memory at the scene of a grisly murder, he soon finds himself hunted by the police, a woman claiming to be his wife, and a mysterious group of pale men.